GRUPA POKOLENIOWA JAKO CZYNNIK RÓŻNICUJĄCY TYP WYTWARZANEGO KAPITAŁU SPOŁECZNEGO W POLSCE - Adamczyk, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In research on social capital, one can observe numerous factors which, on the one hand, condition the creation of social capital assets and, on the other, the occurrence of specific types of these assets. One of the factors which influence significantly the dominance of one type of social capital over others in a given community can be linked to the age structure characteristic of such community. A generation change, combined with the change of the social context, entails transformation in the sphere of values which, in turn, has substantial impact on the behaviour of and actions undertaken by the members of such community. The current article offers an analysis of the transformation of social capital in Poland under the influence of the generation change. The analysis is based on the comparison of two generations of Poles growing up in socially, politically and economically disparate periods.